Cholecalciferol levels, inflammation and leukocytes parameters: Results from a large single-centre cohort of patients. Issue 4 (April 2021) - Verdoia, Monica; Nardin, Matteo; Rolla, Roberta; Negro, Federica; Gioscia, Rocco; Saghir Afifeh, Arraa Maddalena; Viglione, Filippo; Suryapranata, Harry; Marcolongo, Marco; De Luca, Giuseppe; ,
Summary: Background: Vitamin D deficiency represents a pandemic health problem with a broad spectrum of clinical implications. Several studies have involved lower levels of vitamin D with inflammatory disorders including cardiovascular, autoimmune and infectious disease. Indeed, the pathophysiological mechanisms are still poorly ascertained. We aimed at evaluating the impact of cholecalciferol (25(OH)D) levels on the biomarkers of acute-phase response and inflammation in a large cohort of patients with cardiovascular disease. Methods: Consecutive patients undergoing coronary angiography were included. Main clinical features and chemistry parameters were assessed at admission. 25(OH)D levels were measured by chemiluminescence immunoassay kit LIAISON® Vitamin D assay (Diasorin Inc, Stillwater, US). Hypovitaminosis D was defined for 25(OH)D < 10 ng/ml. Results: A total of 3974 patients were included, of whom 29.4% had hypovitaminosis D. 25(OH)D deficiency was associated to age, female gender, diabetes mellitus, renal failure, previous percutaneous coronary intervention and smoke, acute presentation, severe coronary disease, higher glycemia and cholesterol and lower hemoglobin and ejection fraction (p < 0.001), higher platelet count (p = 0.004) and BMI (p = 0.05). 25(OH)D significantly directly related with white blood cells count and the different components of leukocytes formula, Neutrophils-to-Lymphocytes Ratio, Monocytes-to-Lymphocytes Ratio and C-reactive protein, but not with lymphocytes levels. In fact, hypovitaminosis D predicted levels above the median for both Neutrophils-to-Lymphocytes Ratio (≥2.56; 57.3% vs. 47.6%; p < 0.001; adjusted OR[95%CI] = 1.28[1.07–1.52; p = 0.007) and Monocytes -to-Lymphocytes Ratio (≥0.33; 59.1% vs. 49.8%; p < 0.001; adjusted OR[95%CI] = 1.3[1.1–1.54; p = 0.002), results were confirmed in major subgroups of patients. Conclusion: The present study demonstrates that, among patients with cardiovascular disease, 25(OH)D deficiency is associated with a higher metabolic and clinical risk profile and with an elevation of cellular and humoral inflammatory parameters. Future dedicated studies should be, therefore, advocated in order to define whether 25(OH)D supplementation can modulate the mediators of the acute phase response and therefore potentially offer clinical and prognostic advantages on a broad spectrum of inflammatory disease.